A Bioinspired Catalytic Oxygenase Cascade to Generate Complex Oxindoles1. Issue 29 (30th May 2014) - Wang, Yao; Bauer, Jonathan O.; Strohmann, Carsten; Kumar, Kamal
Abstract Catalytic, selective, and controlled oxidative functionalization of CH bonds using molecular oxygen as an oxidant remains highly desirable and equally challenging in the development of synthetic methodologies. Presented herein is a one‐pot oxygenase cascade reaction wherein a copper(I)‐catalyzed oxygenase reaction transforms the allylic methyl group in 3‐methylidene oxindoles into an aldehyde, which then undergoes an aldol–oxa‐Michael addition sequence with β‐ketoesters to yield dihydrofuran‐bearing oxindoles.